Revitalisasi Hukum Keluarga Islam untuk Memberdayakan Ekosistem Ekonomi Syariah yang Adil: Perspektif Normatif dan Socio legal - Ali, Nur; Saputri, Apik Anitasari Intan (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This article explores the critical role of Islamic family law in supporting the development of a just and sustainable Sharia economic ecosystem. It argues that revitalizing core principles of Islamic family law particularly those related to inheritance, marriage, and economic roles within families can significantly influence socio-economic empowerment and gender equity. Through a normative and socio-legal approach, this study examines how legal frameworks can better integrate family institutions into economic empowerment strategies, particularly in Muslim-majority societies. By addressing structural injustices and enhancing legal access for women and marginalized groups, Islamic family law can serve as a catalyst for inclusive economic justice within the broader Islamic economic system.